Working a democratic constitution: the Indian experience - Austin, Granville (New Delhi, 2000)
This important book offers critical insights into four decades of the Indian Constitution. It charts the course of constitutional reform in India from the euphoric idealism of the post-independence period, through the crisis years of emergency, and up to Rajiv Gandhi's brief stay in power. The book analyzes the ways in which various legal and political vicissitudes of democracy have affected the making of the Indian Constitution.
Keywords: Constitution-India-Democratic state